2018
DOI: 10.3892/mmr.2018.8825
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechingallate attenuates myocardial injury in a mouse model of heart failure through TGF‑β1/Smad3 signaling pathway

Abstract: The present study aimed to assess the protective effect of epigallocatechingallate (EGCG) against myocardial injury in a mouse model of heart failure and to determine the mechanism underlying regulation of the transforming growth factor-β1/mothers against decapentaplegic homolog 3 (TGF-β1/Smad3) signaling pathway. Mouse models of heart failure were established. Alterations in ejection fraction, left ventricular internal diastolic diameter (LVIDd) and left ventricular internal systolic diameter (LVIDs) were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
(37 reference statements)
2
21
0
Order By: Relevance
“…Recent animal studies confirm that EGCG significantly inhibits the inflammation in HF by disrupting the functioning of this particular signalling pathway. This correlates with the reduction in plasma concentrations of BNP and NT-proBNP, with improvement of left ventricular systolic function and of left ventricular dimensions, as well as with a survival index in this group of animals with HF [58]. The results of these studies give a preliminary theoretical basis for the treatment of the TGF-Beta1/Smad3 signalling pathway as a potential therapeutic target in HF.…”
Section: The Role Of the Tgf-beta1/smad3 Signalling Pathway In Inflamsupporting
confidence: 64%
See 3 more Smart Citations
“…Recent animal studies confirm that EGCG significantly inhibits the inflammation in HF by disrupting the functioning of this particular signalling pathway. This correlates with the reduction in plasma concentrations of BNP and NT-proBNP, with improvement of left ventricular systolic function and of left ventricular dimensions, as well as with a survival index in this group of animals with HF [58]. The results of these studies give a preliminary theoretical basis for the treatment of the TGF-Beta1/Smad3 signalling pathway as a potential therapeutic target in HF.…”
Section: The Role Of the Tgf-beta1/smad3 Signalling Pathway In Inflamsupporting
confidence: 64%
“…In the animal HF model, it was also confirmed that the intensity of the inflammatory process within the myocardium is significantly reduced by inhibiting the TGF-Beta1/Smad3 signalling pathway [58]. Elevated serum concentrations of proinflammatory cytokines such as interleukin-1Beta (IL-1Beta), IL-6 and TNF-alpha, which are typical in HF, were significantly reduced by treatment with epigallocatechin gallate (EGCG), a substance that strongly inhibits the TGF-Beta1/Smad3 signalling pathway [58]. EGCG is a catechin, i.e.…”
Section: The Role Of the Tgf-beta1/smad3 Signalling Pathway In Inflammentioning
confidence: 73%
See 2 more Smart Citations
“…The results showed that when we inhibited this pathway, the apoptosis rate of cardiomyocytes induced by H/R reduced obviously, and the Bax and activated Cle-Caspase-3 protein expression levels reduced dramatically, but the Bcl-2 protein expression increased greatly. Research [26] has also confirmed that the apoptosis rate of cardiomyocytes can be reduced by inhibiting this pathway in HF mouse model. This also confirms our conclusion.…”
Section: Discussionmentioning
confidence: 84%